Pandemic Experts. On the Transformation of Values and Evaluations in the Practice of Science and its Science Educational Dissemination in the Media in Poland During the Covid-19 Pandemic - Łukasik-Turecka, Agnieszka (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The SARS-CoV-2 coronavirus pandemic has forced changes in many areas of human life activity, also in the field of science, educating students and popularization knowledge. These changes were avalanche-like. Sudden increase in the incidence and introduction due to the pandemic situation, regulations at both national and university levels caused impossiblity to prepare for changes in the areas related to science. They had to be dradually introduced. The aim of this article is to show the changes in the area of values in the practice of science and its dissemination in the media. Tools that worked well during the pandemic are still being used despite cancellation of the epidemic threat, of course to a lesser extent. In in the area of dissemination of expert knowledge, solutions adopted during successive waves pandemics are still applied; experts are invited to the studio, but they often connect with editorial staff using various communicators to disseminate via the media knowledge of your discipline. With the transfer of the work of academics to the Internet, both related to conducting research, educating students, and disseminating knowledge in the media were associated with a number of problems, the most serious in the area of research, but also strongly felt in the area of education. In turn, in the area popularization of science, dissemination of expert knowledge, these changes are strongly related to changes that have been introduced due to the pandemic situation in the media electronic, and have brought many benefits. The biggest of them seems to be expanding the group media experts about dormitories from outside the town whose TV stations or radio stations have a professional studio. In a situation of great demand for information on the SARS-CoV-2 virus and ways to prevent the disease, medical experts and professionals shared their knowledge in the media and straightened it out via communicators fake content spread by disinformers.